BATASAN PENGGUNAAN HIJAB DALAM KONTEKS LITA’?RAF? - baihaqi (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
Chlotingis an identity that attaches to the wearer, because by clothes, humans will have a certain impression, when they see others. A neat and good clothes will certainly give the impression that the person he sees is someone who has good identities. Of course in the case of clothes, Islam provides a rule called syar'iclothes. Where the wearer must cover the genitals (aurat) that has been conveyed by Islam.The use of syar'i clothes in this era has entered the public area, even some b eauty brands in Indonesia have no longer been reluctant to use religious language terms, such as the use of the hijab word in their products, although sometimes its use is not necessarily correct, at least it has given the impression that the Indonesian people have an awareness of the importance of clothes that cover genitals, and lately it is very common to find out that the reason for covering up genitalia must limit to know each other because they have to wear veils (hijab) on their faces. Based on the rule of islam (Syar'i), of course those who wear hijab have their own reasons and their own arguments, but when it comes to dealing with public law, where all citizens must have an identity card which requires photos, of course the identity card requires photos, so it will be difficult for law enforcers and the people serving in the public area to ensure whether the identity card shown is in accordance with the owner, and certainly the communication attitude to know each other will not work well.